External Criticism by Parents and Obsessive Beliefs in Adolescents: Mediating Role of Beliefs Associated With Inflated Responsibility - Halvaiepour, Zohreh (Glob J Health Sci, 2016)
BACKGROUND AND OBJECTIVES: Obsessive-compulsive disorder (OCD) is considered as a rare disorder in children. According to cognitive theories, criticism triggers responsibility behavior and thus causes obsessive behaviors. The purpose of the present study was to investigate the mediating role of beliefs associated with responsibility in the relationship between external criticism of parents and obsessive beliefs in adolescents. MATERIALS AND METHODS: In this study, 547 high school students aged from 15 to18 years were selected using multi-stage cluster random sampling from four regions of the education office in Shiraz. Obsessive Beliefs Questionnaire-child version (OBQ-CV), Pathway to Inflated Responsibility beliefs Scale (PIRBS), and perceived criticism questionnaire were used to collect data. Pearson’s correlation was used to investigate the relationship between the study variables. For analysis of mediation model, multiple mediators analysis using Macro Software was used. RESULTS: External criticism only indirectly and through beliefs associated with inflated responsibility accounts for 6% of the variance of responsibility, 14% of the variance of threat estimation and 10% of the variance of perfectionism of obsessive beliefs (P<0.05). However, external criticism, both directly and indirectly and through beliefs associated with inflated responsibility accounts for 7% of the variance of the importance of obsessive beliefs. CONCLUSION: This study showed that the beliefs associated with inflated responsibility can mediate the relationship between external criticism and obsessive beliefs. According to the cognitive model of Salkovskis, criticism by parents, as a violation to and an influence on children, by affecting the subscales of inflated responsibility, can increase the symptoms of obsessive-compulsive disorder. In order to identify potential affecting mechanisms of criticism on obsessive-compulsive disorder, further experimental research is required.